A permanent, asymmetric dust cloud around the Moon - Horányi, Michály; Szalay, J. R.; Kempf, S.; Schmidt, J.; Grün, Eberhard; Srama, R.; Sternovsky, Z. (Nature, 2015)
Observations are reported of a permanent, asymmetric dust cloud around the Moon, caused by impacts of high-speed cometary dust particles on eccentric orbits, as opposed to particles of asteroidal origin following near-circular paths striking the Moon at lower speeds.